2020
DOI: 10.24843/soca.2020.v14.i03.p09
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Horticultural Farmers Groups in Malang Regency and Batu City

Abstract: The development in the agricultural sector required an increase in human resource capacity. The special effort can be in the form of training and skills in processing agricultural products. The research aim was to analyze the factors that influence the dynamics of horticultural farmers groups, and assessed the level of group dynamics and the independence of horticultural farmer group members. The determination of the location of the research was performed by using a qualitative descriptive method, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Furthermore, supported with qualitative data as a document study. According to Bakhtiar et al, (2020), the descriptive analysis describes data results based on obtained facts. Variables in this research are insight and standpoints, which are measured by Likert scales with five categories comprising very disagree (1), disagree (2), uncertain (3), agree (4), very agree (5).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, supported with qualitative data as a document study. According to Bakhtiar et al, (2020), the descriptive analysis describes data results based on obtained facts. Variables in this research are insight and standpoints, which are measured by Likert scales with five categories comprising very disagree (1), disagree (2), uncertain (3), agree (4), very agree (5).…”
Section: Methodsmentioning
confidence: 99%
“…Trebbin (2014) states that the role of the organization was very limited in helping the farmers' position in the supply chain to supermarkets. The study conducted by Bakhtiar et al (2020) showed that the dynamic value of the horticultural group in Malang was in the high category. It was different from this study in a way that this study did not look at the dynamics in the context of agribusiness development but in the context of farming.…”
Section: Institutional Dynamicsmentioning
confidence: 99%
“…The researchers mostly studied the dynamics of farmer groups and variables related to these dynamics and did not see them as an important aspect of empowering farmers based on their internal strength (Bakhtiar et al, 2020); (Wahyuni et al, 2017). As far as we know, there has been no study comparing the farmer institutional dynamics developed by the government and NGOs in Indonesia and having to do with the vegetable agribusiness development.…”
Section: Introductionmentioning
confidence: 99%
“…Human resources in the context of a farmer group that operates in the agricultural sector, according to some of the above theories, can be defined as people involved in the group, especially administrators who have function as the driver in the group, building the relationship among group members, managing and developing the group [19]. For this reason, human resources who act as a driving force must be the qualified peoples, have skills, work abilities, and high entrepreneurial spirit to achieve the targets and goals of farmer groups.…”
Section: Human Resourcesmentioning
confidence: 99%